Inelastic electron irradiation damage in hexagonal boron nitride. (May 2015) - Cretu, Ovidiu; Lin, Yung-Chang; Suenaga, Kazutomo
Highlights: Inelastic electron damage in h-BN is strongly influenced by temperature. The mechanism responsible for this electron irradiation damage is charging. This damage can be prevented by overlapping h-BN with graphene. Abstract: We present a study of the inelastic effects caused by electron irradiation in monolayer hexagonal boron nitride (h-BN). The data was obtained through in situ experiments performed inside a low-voltage aberration-corrected transmission electron microscope (TEM). By using various specialized sample holders, we study defect formation and evolution with sub-nanometer resolution over a wide range of temperatures, between −196 and 1200 °C, highlighting significant differences in the geometry of the structures that form. The data is then quantified, allowing insight into the defect formation mechanism, which is discussed in comparison with the potential candidate damage processes. We show that the defect shapes are determined by an interplay between electron damage, which we assign to charging, and thermal effects. We additionally show that this damage can be avoided altogether by overlapping the samples with a monolayer of graphene, confirming this for h-BN and providing a way to overcome the well-known fragility of h-BN under the electron beam.